PERSEPSI MAHASISWA PENDIDIKAN TEKNIK OTOMOTIF FT UNY TERHADAP PELAKSANAAN MICRO TEACHING ONLINE - Muhammad Fachri; Joko Sriyanto (Journal of Automotive Technology and Education, 2024)
This study aims to determine the level of perception of students of Automotive Engineering Education FT UNY on the implementation of micro teaching online. This type of research is descriptive with a mixed methods approach, and the research design used is the explanatory sequential design. This research was conducted at the Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University. The population in this study was the Automotive student class of 2018 with a total of 70 people. The sampling technique used in this research is the method developed by Isaac and Michael with an error rate of 1% so that the sample size of students is 63 students. The number of interview samples was 10 students. Research data collection using questionnaires and interviews. Construct validity using expert judgment was used to obtain the validity of the data, and also the Readability Test for a sample of students. The collection and analysis of questionnaire data used a quantitative method in the first stage, and was followed by the collection and analysis of interview data using a qualitative method in the second stage. The results in the study are the perceptions of students of Automotive Engineering Education FT UNY on the implementation of online micro teaching as a whole including in the good category with a percentage of 69.83%, in detail the acceptance indicator is in the good category with a percentage of 72.39%; The understanding indicator is included in the good category with a percentage of 68.85%; Evaluation indicators are included in the good category with a percentage of 68.25%. There are also perceptions from students who are not good, some findings of weaknesses and obstacles from online micro teaching learning include: (1) students have problems with slow internet networks or signals, (2) practical teaching practice exercises are not effective and not optimal, because the material and practicum tools owned by students are limited, (3) students feel that their ability to teach practicum is not honed, because the method of giving assignments from lecturers is only limited to looking for animations. (4) online micro teaching learning makes students bored because of difficulties in interacting with classmates.